Dilema Penambangan Dasar Laut: Pengaturan Dalam ISA, Prinsip Kehati-Hatian dan Tantangan Implementasi Perjanjian BBNJ - Adrian Nugraha; Nashriana Nashriana; Ridwan Ridwan (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2025)
This article examines the role of the International Seabed Authority (ISA) in the governance of deep seabed mining, highlighting the legal and environmental implications arising from the adoption of the Biodiversity Beyond National Jurisdiction (BBNJ) Agreement in 2023. The research employs a normative juridical method through an extensive review of international legal instruments, doctrines, jurisprudence, and scholarly literature related to the United Nations Convention on the Law of the Sea (UNCLOS) 1982, the precautionary principle, and global environmental agreements. The analysis reveals that the ISA’s mandate to manage seabed resources as the common heritage of mankind faces significant pressure due to growing scientific evidence of the ecological risks associated with deep-sea mining. Potential jurisdictional and normative conflicts also arise between the ISA and BBNJ regimes, particularly concerning marine protected areas, environmental impact assessments, and access to marine genetic resources. In the context of scientific uncertainty, mineral exploitation may violate the precautionary principle, erga omnes obligations, and the commitments of Sustainable Development Goal 14. Accordingly, this study recommends a moratorium on mining activities, the harmonization of ISA–BBNJ legal frameworks, and the strengthening of implementation of the precautionary principle to ensure the sustainability of deep-sea ecosystems.